UPAYA MENINGKATKAN HASIL BELAJAR EKONOMI MELALUI MODEL PEMBELAJARAN LEARNING CYCLE PADA PESERTA DIDIK SMA GAJAH MADA - Kurniawan, Komang Hendri; RB, Muhammad; Idham, M (LPPM STKIP PGRI Bandar Lampung, 2020)
The problem that was found by the writein in X grade of IPS 4 Gajah Mada senior High School Bandar Lampung is the low activity of students and student learning outcomes during the learning process in the classroom. In this study the author uses a Learning Cycle learning model that is expected to improve the activity and economic learning outcomes of X. IPS 4 students on economic subjects at Gajah Mada High School Bandar Lampung Academic Year 2018 / 2019. This study is a classroom action research ) conducted in two stages of the cycle in which the application uses the Learning Cycle learning model in the learning process. The subjects in this study were students of class X. IPS 4, Gajah Mada High School, Bandar Lampung, amounting to 36 students. student learning has increased from an average of 2.1 in cycle 1 to 3.61 in the cycle 2. The percentage of students' learning completeness increased from pre-cycle to 27.78%, cycle 1 was 52.78% and cycle 2 was 81 %. From the results of the analysis, it can be concluded that learning by implementing a Learning Cycle model can improve learning activities and economic learning outcomes of class X students. IPS 4 SMA Gajah Mada Bandar Lampung Academic Year 2018/2019